Honokiol Inhibits Atrial Metabolic Remodeling in Atrial Fibrillation Through Sirt3 Pathway - Liu, Guang Zhong; Xu, Wei; Zang, Yan Xiang; Lou, Qi; Hang, Peng Zhou; Gao, Qiang; Shi, Hang; Liu, Qi Yun; Wang, Hong; Sun, Xin; Liu, Cheng; Zhang, Peng; et al. (Frontiers in Pharmacology, 2022)
BACKGROUND AND PURPOSE Atrial metabolic remodeling is critical role in the pathogenesis of atrial fibrillation (AF). Sirtuin3 (Sirt3) plays an important role in energy homeostasis. However, the effect of Sirt3 agonist Honokiol (HL) on AF is unclear. Therefore, the aim of this study was to determine the effect of HL on atrial metabolic remodeling in AF and to explore possible mechanisms. EXPERIMENTAL APPROACH Sirt3 and glycogen deposition in left atria of AF patients were examined. Twenty-one rabbits were divided into sham, P (pacing for 3 week), P+H treatment (honokiol injected with pacing for 3 week). The HL-1 cells were subjected to rapid pacing at 5 Hz for 24 h, in the presence or absence of HL and overexpresion or siRNA of Sirt3 by transfection. Metabolic factors, circulating metabolites, atrial electrophysiology, ATP level, glycogens deposition were detected. Acetylated protein and activity of its enzymes were detected. KEY RESULTS Sirt3 was significantly down-regulation in AF patients and rabbit/HL-1cell model, resulting in the abnormal expression of its downstream metabolic key factors, which was significantly restored by HL. Meanwhile, AF induced an increase of acetylation level in LCAD, AceCS2 and GDH, following decreasing of activity of it enzymes, resulting in abnormal alterations of metabolites and reducing of ATP, which was inhibited by HL. The Sirt3 could regulate acetylated modification of key metabolic enzymes, and increased of Sirt3 rescued AF induced atrial metabolic remodeling. CONCLUSION AND IMPLICATIONS HL inhibited atrial metabolic remodeling in AF via Sirt3 pathway. The present study may provide a novel therapeutical strategy for AF.